Phytotoxic Extracts as Possible Additive in Subsurface Irrigation Drip for Organic Agriculture - Romanucci, V.; Ladhari, A.; Tommaso, G. De; Marco, A. De; Marino, C. Di; Fabio, G. Di; Zarrelli, A. (Journal of Environmental Accounting and Management, 2026)
The subsurface drip irrigation (SDI) system is a micro-irrigation technique applied below the soil surface through drip lines buried at a depth depending on the characteristics of the soil and on the plants to be irrigated. SDI distributes precise amounts of water directly to the root area, with the possibility of leaving the soil surface dry and less subject to weeds. This system reduces the use of water, herbicides, and environmental pollution. Furthermore, SDI allows the use of urban wastewater, advantageous from the environmental point of view since it reduces the consumption of ground water and energy costs required for its pumping. In addition, it reduces the use of chemical fertilizers through the enhancement of organic fertilizer content in the waste. However, there are issues related to the use of SDI systems, such as the elimination or reduction of roots that wrap the dripper thus blocking the water flow. It has been hypothesized that it would be useful to add a pure or blended phytotoxic mixture to plastic during the production of drippers, whose herbicidal action dissolves gradually with the passage of water. Five species of plants have been selected in this study: Vetch villosa, Brassica juncea, Secale cereale, Juncus effusus, and Vallisneria natans. The phytotoxicity has been tested in vivo on Lactuca sativa, Lycopersicon esculentum, and Allium cepa. The plants showed the same behavior but the aerial biomass of V. natans resulted the most active ones. The phytotoxicity of the hydroalcoholic extract of each plant was evaluated on the same test organisms, with peak inhibitions up to 60, 70, and 80% at concentrations ranging from 10-4 to 10-7M. In general, the most active hydroalcoholic infusion was that of V. villosa. Finally, after some chromatographic steps and LC/GC-MS analyses, the most abundant metabolites of the hydroalcoholic extracts were identified.